Re-presenting Disability in Cinema: A Semiotic Study of Srikanth Based on John Fiske’s Framework - Fatimah Bilqis; Eko Hari Saksono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the representation of disability in the film Srikanth through John Fiske's semiotic approach. Using a qualitative method and media text analysis technique, the study explores the three levels of semiotic codes developed by Fiske: the codes of reality, representation, and ideology. The analysis reveals that Srikanth presents the narrative of a visually impaired individual not merely as an object of pity, but as a subject with agency, resilience, and a strategic role in society. At the level of reality codes, the character Srikanth is represented through body language, facial expressions, and dialogues that emphasize independence. The representation codes highlight how cinematography, props, and characters are constructed to build a positive image of disability. Meanwhile, the ideological codes convey values of inclusivity and the recognition of the rights of people with disabilities. This study affirms that Srikanth serves as a significant example in shifting the paradigm of disability representation in mainstream media, from stereotypical portrayals to more humanizing and empowering narratives.